Indonesia’s Culinary Evolution: From Street Food to Michelin Stars - Dexter, Angeline; Qomariah, Nur; Zaiddurrohman, Muhammad (Universitas Negeri Semarang, 2024)
This study explores the dynamic transformation of Indonesia’s food culture, tracing its journey from humble street food stalls to internationally acclaimed fine dining establishments. This research delves into the social, cultural, and economic factors that have shaped Indonesia’s culinary scene, highlighting how traditional flavors and techniques have been reinterpreted in contemporary settings. The study examines the growing recognition of Indonesian cuisine on the global stage, particularly in light of the recent introduction of Michelin stars in the country. By investigating the fusion of local ingredients with international cooking methods, the research underscores the significance of culinary innovation in elevating Indonesia's food culture. The analysis focuses on key moments of change, such as the rise of high-end Indonesian restaurants, the increasing influence of food media, and the integration of culinary tourism in the national economy. The study also emphasizes the role of street food in preserving Indonesia’s cultural identity while driving culinary experimentation. This research contributes to a deeper understanding of how globalization and modernization intersect with traditional food practices, offering insights into the role of food in national identity and cultural pride. Additionally, it addresses the challenges and opportunities facing Indonesia’s culinary industry, including sustainability, cultural preservation, and the balancing of tradition with modernity. By tracing Indonesia’s culinary evolution, this work highlights the importance of food as a key element of cultural diplomacy and economic development in the globalized world.